Responses of human dental pulp cells after application of a low-concentration bleaching gel to enamel - Soares, Diana G. [UNESP]; Basso, Fernanda G. [UNESP]; Scheffel, Débora Salles [UNESP]; Hebling, Josimeri [UNESP]; de Souza Costa, Carlos A. [UNESP] (Elsevier B. V., 2015)
To evaluate the effect of a 17.5% H2O2 gel on the odontoblastic differentiation capability of human dental pulp cells (HDPCs). The bleaching gel was applied for 45, 15 or 5min to enamel/dentine discs adapted to transwells, positioned over previously cultured HDPCs. In the control group, no treatment was performed on the discs. Immediately after samples were bleached, the cell viability (MTT assay) and death (Live/Dead assay) as well as the mRNA gene expression of inflammatory mediators (TNFα, IL-1β, IL-6, and COX-2; real-time PCR) were evaluated. The mRNA gene expression of odontoblastic markers (DMP-1, DSPP, and ALP) and mineralized nodule deposition (alizarin red) were assessed at 7, 14 and 21 days post-bleaching. The amount of H2O2 in contact with cells was quantified. Data were evaluated by Kruskal-Wallis and Mann-Whitney tests (α=5%). Significant cell viability reduction and cell death were observed for bleached groups relative to control in a time-dependent fashion. Also, significant overexpression of all inflammatory mediators tested occurred in the 45- and 15-min groups. In the bleached groups, the expression of ALP, DMP-1, and DSPP and the deposition of mineralized nodules were reduced in comparison with those in the control group, at the initial periods (7 and 14 days). However, the 15- and 5-min groups reached values similar to those in the control group at the 21-day period. The 17.5% H2O2 gel was cytotoxic to pulp cells; however, cells subjected to short-term bleaching are capable of expressing the odontoblastic phenotype over time.
Keywords: Dental pulp; Differentiation; Hydrogen peroxide; Odontoblasts; Tooth bleaching